Pengaruh Pendapatan Margin Murabahah dan Pendapatan Bagi Hasil Musyarakah terhadap Laba Bersih - Ai Iklimah Agustina; Sulaeman Sulaeman; Tina Kartini (Al Maal: Journal of Islamic Economics and Banking, 2021)
The purpose of this study to know the effect of murabahah margin revenue and musyarakah profit sharing revenue on BRI Syariah and BJB Syariah net profit. The object of research in this study is 4 years of financial statements at Islamic Commercial Banks in Indonesia especially BRI Syariah and BJB Syariah. The research method used in this study is a quantitative method with an associative approach. The sample used the Nonprobability Sampling approach with the Purposive Sampling method, From 14 Islamic Commercial Banks in Indonesia, 2 banks were chosen with 32 sample financial reports per quarter. Data collection techniques are to use secondary data, namely with documentation and study of literature. The data analysis technique used in this study is multiple linear regression. The results of this study indicate a significant positive effect of murabahah margin income on net profit, there is no significant effect of musyarakah profit sharing revenue on net profit. And the positive influence jointly from murabahah margin income and musyarakah profit sharing revenue significantly, with an influence level of 80.7% and the remaining 19.3% are other variables that also influence net profit but are not examined in this study